Answer:
see explanation
Step-by-step explanation:
The translation rule
(x, y ) → (x + 3, y - 2 )
Means add 3 to the original x- coordinate and subtract 2 from the original y- coordinate, thus
A(- 4, 1 ) → A'(- 4 + 3, 1 - 2 ) → A'(- 1, - 1 )
B(1, 1 ) → B'(1 + 3, 1 - 2 ) → B'(4, - 1 )
C(1, - 2 ) → C'(1 + 3, - 2 - 2 ) → C'(4, - 4 )
D(- 4, - 2 ) → D'(- 4 + 3, - 2 - 2 ) → D'(- 1, - 4 )
I needa see it tho for I could help
Answer:
This is one of many possible answers.
(x -1)(x-2)(x-3)
Explanation:
The zeros are x = 1, x = 2, x = 3. This polynomial has a degree of 3.
9/10 i the answer i believe